Seasons of a Finger Lakes winery - Hartsock, John C., 1951- (Cornell University Press, 2011)
In 1998, Gary and Rosemary Barletta purchased seven acres of land on the eastern shore of Cayuga Lake. Descending to the west from the state route that runs along on the ridge overlooking the lake, the land was fertile, rich with shalestone and limestone bedrock, and exposed to moderating air currents from the lake. It was the perfect place to establish a vineyard, and the Barlettas immediately began to plant their vines and build the winery about which they had dreamed for years. The Barlettas' story, as John C. Hartsock tells it, is a window onto the world of contemporary craft winemaking, from the harsh realities of business plans, vineyard pests, and brutal weather to the excitement of producing the first vintage, greeting enthusiastic visitors on a vineyard tour, and winning a gold medal from the American Wine Society for a Cabernet Franc. Above all, Seasons of a Finger Lakes Winery describes the connection forged among the vintner, the vine, and terroir. This ancient bond, when tended across the cycle of seasons, results in excellent wines and the satisfaction, on the part of the winemaker and the wine enthusiast, of tasting a perfect harvest in a single glass. Today, Long Point Winery sits on seventy-two acres (eight of which are under cultivation with vinifera grapes) and produces sixteen varieties of wine, a number of which are estate wines made from grapes grown on their property. With interest in winemaking continuing to grow, the Barlettas' experience of making award-winning wines offers both practical advice for anyone running (or thinking of running) their own winery, whether in the Finger Lakes or elsewhere, as well as insights into the challenges and joys of pursuing a dream.